Help and cooperation in the light of the Prophet’s ﷺbiography: المساعدة والتعاون في ضوءسيرة النبويةﷺ - Muhammad Akram, makram (AL-IDRAK JOURNAL, 2021)
Cooperation is a necessity of life; As the One man cannot fulfill all the burdens of this life alone. And God has made cooperation a fitrah in all his creatures. Cooperation is an imperative in a single society, just as it is necessary between peoples and nations. Complete and comprehensive reform can only be achieved with the cooperation of all forces. As stated in the message of the sixth conference of the Muslim Brotherhood: As for the Brotherhood’s primary goal. As for the Brotherhood’s ultimate goal ۔ As for the reform that the Brotherhood wants and prepares for itself .. It is a comprehensive and complete reform on which the forces of the entire nation collaborate. And all nation heads towards him. We search different images with help, and cooperate in the light of the Prophet’s biography as Cooperation between Muslims, cooperation in the home and engagement with his wives, scientific cooperation, political cooperation, moral cooperation, reform cooperation, literary cooperation, cooperation in building the mosque, and cooperation in digging the trench۔